USO DE PLATAFORMAS Y HERRAMIENTAS DIGITALES PARA MEJORAR EL PROCESO DE APRENDIZAJE EN EL ÁREA DE MATEMÁTICAS EN LOS ESTUDIANTES DEL OCTAVO AÑO DE EDUCACIÓN BÁSICA EN LA UNIDAD EDUCATIVA OSWALDO VILLAMIL AUZ DEL CANTÓN QUEVEDO EN EL PERIODO LECTIVO 2022. - SONIA MARÍA CHICA MACAY (2022)
The present research study focuses on the implementation of platforms and digital tools in the application of technologies in the teaching process to students in the area of mathematics, with the objective of determining the incidence of the use of platforms and digital tools in learning in the area of mathematics in students of the eighth year of General Basic Education of the Oswaldo Villamil Auz Educational Unit of the canton Quevedo in the school year 2022. However, from the methodological aspect, it has a non-experimental design with a quantitative approach, where data collection is developed as a result of the proposed instruments, to respond to the established objective through the statistical analysis of the proposed questions. That is why it is of an explanatory, descriptive, field and bibliographic type, where the analytical, synthetic, inductive and deductive methods are applied for the development of the research conformed by a population of 40 students of the eighth year of Basic Education. Therefore, it is concluded that in the development of the literary review according to the variables and dimensions that are emphasized within the theoretical and conceptual framework to justify the importance and relevance of the research. It allowed the researcher to contextualize the different platforms and digital tools for the improvement of mathematics in high school students